GIOTTO IN RUSSIAN POETRY: NEGATIVITY, DESIGN AND CONSTRUCTION OF SOCIETY (Philological Studies, 2020)
The perception of Giotto’s heritage in Russian literature and culture has always been directly linked not only with the concept of the Renaissance and the development of Western culture, but with a special interest in writing practice and in the ambition of the narrative presented as innovative style to create communities. The main topic of the poetic thought was the transition from community to society, in other words, from community to church, so Giotto's status as a genius was always supported with statements about other geniuses who directly, but rather indirectly, made this transition. Despite the scarcity of references to the name Giotto, Russian poetry did not so much reflect the current art history conception, but anticipates or corrects conclusions of art historians. My careful analysis of the statements about Giotto in Russian poetry (V. Komarovsky, S. Soloviev, A. Voznesensky) in comparison with the conclusions of Russian philosophy and humanities (P. Florensky, P. Muratov, P. Bitsilli, V. Lazarev) explains plots of the poems related to picturesque impressions. The technique of chiaroscuro in Giotto, who first began to convey plausible depth through the illusory distribution of light, was understood as a technique primarily of hint and reflection, a negative, in comparison with which later Italian painting looks like a colorful positive. Such concept did not correspond to Giotto's real place in the history of art, but it did make it possible to correlate Giotto with Byzantine and Old Russian art using a golden background, emphasizing in the legacy of the Italian artist not credibility, but ability to create own art project relevant other projects.
Keywords: Giotto; ekphrasis; descriptive poetry; the social function of art; reform in art; historicism